Zbrodnie wojenne na morzu pełnym w procesach po I i II wojnie światowej - Kaczmarek, Kinga (Uniwersytet Wrocławski Koło Doktryn Politycznych i Prawnych, 2023)
The article presents war crimes on the high seas during the world conflicts of 1914-1918 and 1939-1945, which were carried out after their end. The evolution of attempts at international settlement of persons suspected of committing war crimes after both world wars has been shown. The article is based on two cases decided by the German Supreme Court in Leipzig, which was to try Germans suspected of committing war crimes during the Great War: the trial of the sinking of HMHS Dover Castle and the trial of officers of the German submarine for torpedoing HMHS Llandovery Castle. The question of the responsibility of Grand Admiral Karl Dönitz and Grand Admiral Erich Raeder for the sinking of SS Athenia and HMS Laconia, which was settled during the Second World War Crimes Trial before the International Military Tribunal at Nuremberg is also described.
Keywords: war crimes; high sea; Supreme Court in Leipzig; the International Military Tribunal at Nuremberg